A Content Analysis of the Offender Population in Counseling Journals. Issue 1 (3rd April 2021) - Rio, Jennifer; Heckman, Lindsay; Tippett, Hannah
Abstract : We discuss the findings of an exploratory content analysis related to the offender population by examining literature from 2008 to 2018 in 23 American Counseling Association (ACA) and ACA‐affiliated counseling journals. The findings and implications of the analysis are discussed.